Moral passion and Christian ethics - Gill, Robin (New studies in Christian ethics, 2017)
Moral passion in new studies in Christian ethics -- Is moral passion germane just to theologians? -- Christian public ethics -- Faith as an option -- Moral outrage -- Collective moral passion within faith traditions -- Moral passion as enemy-love